NEWEST APPROACHES TO THE DIAGNOSIS OF HYPERPLASTIC PROCESSES IN GYNECOLOGY - Doroshenko-Kravchyk, M.V. (World of Medicine and Biology, 2020)
The efficacy of elastography as an additional diagnostic method in the ultrasound examination of the pelvic organs in patients with hyperplastic processes of the uterus and endometrium was studied. 75 women of reproductive age from 24 to 40 years with hyperplastic processes of the uterus and endometrium were examined. Of these, 20 women had diffuse-nodal, diffuse or nodal forms of uterine fibroids, 15 – endometrial hyperplasia, 17 – uterine polyps, 23 –adenomyosis. General clinical studies, ultrasound of the pelvic organs with elastography using General Electric Voluson E8 ultrasound apparatus were performed. At suspicion of an atypical etiology of processes, the histopathological study was carried out. It was shown that ultrasound elastography was an additional method of examination and allowed to differentiate hyperplastic processes of the endometrium from oncologic processes and to estimate the depth of invasion process, clarified the diagnosis of the myometrium condition in adenomyosis with clear verification of invasion sites. Verified the morphological etiology of uterine polyps. Diagnosed the condition of nodal diffuse proliferation in uterine leiomyoma to monitor conservative management and treatment.
Keywords: elastography; proliferative processes; adenomyosis; leiomyoma; polyp